The Realization of Village, Education, and Health Funds to Reduce Poverty in Eastern Indonesia - Tamba, Helena Louisa Andriani; Shen, Ming; Nugraheni, Siwi; Sigiro, Ely Elprida; Nafisa, Ferinda (Faculty of Economics and Business Universitas Jenderal Soedirman, 2024)
Village funds are used to improve the welfare of rural communities and develop various regions in Indonesia, including the 3T (frontier, remote, and disadvantaged) areas in Eastern Indonesia. Therefore, this study uses the Panel Least Square method to see the consequence of village, education, and health funds on poverty levels, especially in 7 provinces in Eastern Indonesia using yearly data 2017-2022. The realization of village funds, education funds, and health funds are used as independent variables, while the percentage of poor people is used as a dependent variable. The study results show that village fund and health fund significantly reduce poverty rates in Eastern Indonesia. Meanwhile, the education fund did not significantly reduce poverty in Eastern Indonesia. Although village and health funds can reduce poverty in Eastern Indonesia, the government should prioritize improving the education level of the region's people to significantly alleviate poverty.